Hijrah: Exploring A New Model of Islamic Education - Nugroho, Aris Dwi; Malik, Abd (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
The problem raised in this paper is how the hijrah or hijrah community in Jambi city becomes a new alternative to Islamic education that is in demand by teenagers, and community groups that often escape the attention of Islamic educational institutions (punks, motorcycle gangs, and so on). The purpose of this study was to obtain empirical data related to the concept of hijrah offered by the hijrah community in Jambi city, and the concept of Islamic education initiated by the hijrah community in Jambi city. This study is a qualitative research, with the subject of research is the hijrah community in Jambi city which amounted to 2 communities, namely the community of Youth Move Up (YMU), and community of Shubuh Fighter. Data collection techniques used are observation, interviews, and documentation. The data analysis technique used is descriptive analysis by describing the process of inductive thinking that departs from specific factors, concrete events and then from specific factors or events and concrete then it is drawn generalizations that are general. This study concludes that; (1) the concept of hijrah initiated by the ymu community and the community of Dawn fighters have differences and similarities. Both communities have the same goals and targets in general, namely millennials, whose goal is for members to migrate from a previous life away from religion to a life that is allowed by religion. The difference lies in the main approach that is specifically implemented by the community of Dawn Fighter, where the community has its own benchmark, that the beginning of the success of the hijrah was preceded by the improvement of Fajr prayer. If the morning prayer is good, then the other affairs will be good too. It will have an impact on you and it will have an impact on others. (2) The concept of Islamic education implemented by the YMU community, and the dawn Warrior community is basically the same, where learning about everyday life is not only carried out face-to-face in an activity, but also through social media platforms; YouTube, Instagram, Facebook and other social media, both in the form of videos, and nonsense. The concept of online activism of this kind makes the emergence of participation to participate in social movements, and is proven to be effective in inviting audiences to be able to follow the same steps. Then he used several approaches, namely the wisdom approach, the psychodynamic approach, and the hobby or pleasure approach.